Bifunctional glycosyltransferases catalyze both extension and termination of pectic galactan oligosaccharides. (22nd March 2018) - Laursen, Tomas; Stonebloom, Solomon H.; Pidatala, Venkataramana R.; Birdseye, Devon S.; Clausen, Mads H.; Mortimer, Jenny C.; Scheller, Henrik Vibe
Summary: Pectins are the most complex polysaccharides of the plant cell wall. Based on the number of methylations, acetylations and glycosidic linkages present in their structures, it is estimated that up to 67 transferase activities are involved in pectin biosynthesis. Pectic galactans constitute a major part of pectin in the form of side‐chains of rhamnogalacturonan‐I. In Arabidopsis, galactan synthase 1 (GALS1) catalyzes the addition of galactose units from UDP‐Gal to growing β‐1, 4‐galactan chains. However, the mechanisms for obtaining varying degrees of polymerization remain poorly understood. In this study, we show that At GALS1 is bifunctional, catalyzing both the transfer of galactose from UDP‐α‐d ‐Gal and the transfer of an arabinopyranose from UDP‐β‐l ‐Ara p to galactan chains. The two substrates share a similar structure, but UDP‐α‐d ‐Gal is the preferred substrate, with a 10‐fold higher affinity. Transfer of Ara p to galactan prevents further addition of galactose residues, resulting in a lower degree of polymerization. We show that this dual activity occurs both in vitro and in vivo . The herein described bifunctionality of At GALS1 may suggest that plants can produce the incredible structural diversity of polysaccharides without a dedicated glycosyltransferase for each glycosidic linkage. Significance Statement: Dedicated transferases have previously been expected to catalyze the formation of each unique glycosidic linkage present in plant cell wall polysaccharides. Here we demonstrate the in‐vitro and in‐vivo activities of a bi‐functional glycosyltransferase capable of integrating both galactose and chain‐terminating arabinopyranose into pectic galactans. The results demonstrate that dedicated glycosyltransferases may not be required for all the glycosidic linkages found in the cell wall.